Worse or even better than expected?: outcome expectancies and behavioral experiences in the context of physical activity among cancer patients - Ungar, Nadine; Rupprecht, Fiona; Steindorf, Karen; Wiskemann, Joachim; Sieverding, Monika (Journal of health psychology, 2021)
Expectancies of cancer patients regarding their physical activity before they took part in a behavior change intervention were compared with their experiences d...
First published March 11, 2019
Gesehen am 16.07.2021